Pemberian Makananan Tambahan pada Bayi Balita dalam Upaya Pencegahan Stunting di Kelurahan Fatukoa Kecamatan Maulafa Kota Kupang - Ahmad, Siti Nur Asyah Jamillah; Henukh, Dina M.S (Program Studi Manajemen FEB UNM, 2023)
Stunting can be prevented by providing additional food in the form of animal protein because of the role of animal protein as a macronutrient which has the best source of essential amino acids that the body needs to activate various enzymes and growth hormones. Therefore, consumption of a variety of animal proteins is currently highly encouraged, especially among vulnerable community groups, namely pregnant women, toddlers and children under 2 years of age and breastfeeding mothers, because these community groups experience a core life cycle which is often referred to as 1000 HPK ( First 1000 Days of Life). At 1000 HPK, if nutritional disorders can be overcome, it can reduce the possibility of malnutrition and stunting in the next period of a child's life. The aim of implementing this activity is to increase the protein adequacy of babies and toddlers and increase mothers' knowledge in preparing animal protein needs for babies and toddlers. The method used in this service is to provide PMT in the form of animal protein directly to the target, while to provide education using the lecture and question and answer method. After carrying out this community service activity, mothers were willing to practice giving animal protein correctly to babies and toddlers at home.